Leveraging on religious and ethical aspects in marketing Takaful products: Malaysian experience - Abdul Aziz, Akhtarzaitie (European Center for Science Education and Research, 2017)
Takaful serves as an alternative for the Muslims to fulfill their insurance needs in a Shariah compliant manner. Participating in a takaful scheme, while aimed mainly at gaining protection against the risks, could also be perceived as a scheme of mutual help. The religious and ethical aspects of takaful can be an attractive value proposition to the people especially Muslims, as in Islam helping those in need with sincere intention for the sake of Allah is an act of piety rewarded by Him. Apart from the inherent spiritual distinctive feature of takaful, takaful products might also provide for other religious contentment. Some takaful products cover debt settlement for the deceased, payment for outstanding zakat, execution of charitable donation or waqaf and even providing for the performance of hajj, which are religiously of tremendous values for the deceased. All these features could be attractive marketing points for takaful especially among the Muslims. This study focuses on the religious and spiritual dimensions of takaful products and explores on the experience of a group of takaful agents of a selected takaful operator in marketing their products by leveraging on these aspects.